METHODOLOGY INTELLIGENT PROCESSING OF AERIAL PHOTOGRAPHS WITH THE RELEASE OF THE KEY FEATURES DECRYPTION - Бараннік, В.В.; Комолов, Д. І. (Science-based technologies, 2016)
This paper developed a method compatibility code construction energetically significant structural unit with the requirement of the method of block symmetric encryption algorithm encryption to close the streaming video technology-based intra-breeding base of the video frame. The methodological basis for calculating the bit rate of the basic structural unit of the encrypted video frame. Schemes of forming bitmap to match the encryption key matrices. Also, encryption is a diagram of a significant structural unit of the base frame. A comparative analysis of the bitstream encoded structural unit in the bit stream of the original video fragment.